2020
DOI: 10.2147/cmar.s255895
|View full text |Cite
|
Sign up to set email alerts
|

<p>Inhibition of CDK1 Reverses the Resistance of 5-Fu in Colorectal Cancer</p>

Abstract: Introduction: Although the survival rate of colorectal cancer (CRC) patients can be improved by surgery, radiotherapy, and chemotherapy, the resistance to 5-fluorouracil (5-Fu) affects the effect of chemotherapy and the prognosis of patients. An increasing number of studies showed that 5-Fu resistance was the main reason for the failure of colorectal cancer treatment. The poor prognosis of colorectal cancer greatly harms people's health. This study aimed to clarify the correlation between cyclin-dependent kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…The research by Yang et al [ 37 ] confirms that CDK1 is associated with cancer growth and the survival rate of epithelial ovarian cancer. Recent findings [ 38 ] show that CDK1 affects 5-Fu resistance in colorectal cancer. Moreover, another study reported that the CDK1/CCNB1 axis can regulate hepatocarcinogenesis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The research by Yang et al [ 37 ] confirms that CDK1 is associated with cancer growth and the survival rate of epithelial ovarian cancer. Recent findings [ 38 ] show that CDK1 affects 5-Fu resistance in colorectal cancer. Moreover, another study reported that the CDK1/CCNB1 axis can regulate hepatocarcinogenesis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of nuclear/cytoplasm (N/C) ratio on these samples showed that high N/C expression is often found in patients with overall worse survival and a N/C > 1.5 can be considered a risk factor. Furthermore, high CDK1 expression is predominant in patients with resistance to 5-fluorouracil (5-Fu), a common CRC treatment, and it seems to reduce the effect of chemotherapy ( Zhu et al, 2020 ). An upregulation of CDK1 in CRC has been also observed in response to other drugs such as: betaxol, penbutolol and propofol amongst others ( Mastrogamvraki and Zaravinos, 2020 ).…”
Section: Cyclin-dependent Kinase Expression In Human Colorectal Cancermentioning
confidence: 99%
“…However, when this cell cycle checkpoint evasion is blocked by CDK1 inhibitors, the cancer cells are less likely to survive (Figure 6). This also explains studies demonstrating that CDK1 inhibition reduces gemcitabine-and 5-FU resistance in multiple different cancer types [73,[80][81][82]. Another study showed that CDK1 inhibition enhanced the ability of the protein kinase inhibitor sorafenib to specifically kill stem cells of hepatocellular carcinoma [41].…”
Section: Combination Therapymentioning
confidence: 79%